Physicians, Patients, and the Electronic Health Record: An Ethnographic Analysis - Ventres, William (Copyright 2006 Annals of Family Medicine, Inc., 2006)
PURPOSE Little is known about the effects of the electronic health record (EHR) on physician-patient encounters. The objectives of this study were to identify the factors that influence the manner by which physicians use the EHR with patients. METHODS This ethnographic study included 4 qualitative components: 80 hours of participant observation in 4 primary care offices in the Pacific Northwest; individual interviews with 52 patients, 12 office staff members, 23 physicians, and 1 nurse-practitioner; videotaped reviews of 29 clinical encounters; and 5 focus-group interviews with physicians and computer advocates. The main outcome measures were factors that influence how physicians use the EHR. Researchers qualitatively derived these factors through serial reviews of data. RESULTS This study identified 14 factors that influence how EHRs are used and perceived in medical practice today. These factors were categorized into 4 thematic domains: (1) spatial—effect of the physical presence and location of EHRs on interactions between physicians and patients; (2) relational—perceptions of physicians and patients about the EHR and how those perceptions affected its use; (3) educational—issues of developing physicians’ proficiency with and improving patients’ understandings about EHR use; and (4) structural—institutional and technological forces that influence how physicians perceived their use of EHR. CONCLUSIONS This study found that the introduction of EHRs into practice influences multiple cognitive and social dimensions of the clinical encounter. It brings into focus important questions that through further inquiry can determine how to make best use of the EHR to enhance therapeutic relationships.